Expansão da fronteira agropecuária e a dinâmica do desmatamento florestal na Amazônia paraense sob a ótica da Nova Economia Institucional - CARVALHO, André Cutrim (Universidade Federal de Campina Grande, 2021)
This paper discusses the problem of deforestation in Pará Amazon forest from the perspective of New Institutional Economics. The discussion of border institutions and governance mechanism(s) is important to structure a historical-institutionalist outlook on this topic. It is observed that the legislative apparatus contained in Operation Amazon gave the Legal Amazon, ie, the border is a product of the creation of the state institution. The basic hypothesis is that the expansion of the agricultural frontier is the central element of forest clearing in the Amazon Pará, and that this progress also includes other factors directly linked to the advance of capitalist economic progress, such as: economic growth, increased herd veal, concentrated land ownership, speculation about the price of land, rural credit institutions, among others. However, the main cause of forest clearing activity in Pará Amazon remains the beef cattle in extensive. In this research, it was found that governance mechanisms adopted in federal and state environmental management policies designed to combat forest clearing, primarily as investments targeted for surveillance, licensing and traceability of bovine chain, contribute effectively to thereducing deforestation in the region.